(untitled) (Research, Society and Development, 2021)
The present research aim was to assess how occlusal contacts change along the initial 6 months of orthodontic treatment with fixed appliance and clear aligners. A sample with 40 patients was divided into 2 groups: Clear Aligners (CA) and Fixed Appliance (FA). In order to register occlusal contacts, patients were posit and instructed about how bite in habitual maximum intercuspidation. Registrations were perfomed monthly along 6 starting treatment months and noted in an occlusogram. A parametric test was applied to evaluate data since it presented a normal distribution according to Shapiro-Wilk test. For inter- and intergroup data analysis the Anova test was performed with a 5% significance level. Statistical tests were executed on Jamovi software (Jamovi Stats, Version1.2, Sydeney, Australia). There was a reduction in the amount of occlusal contacts for indivduals from both groups, CA and FA. Such reduction was more significative in the 3 starting months for FA group and between 3rd and 4th months for CA group. Therefore, the sort orthodontic appliance had no significant influence over occlusal contacts.